Sarekat Islam and the Anti-Chinese Riots - M. Nasihudin Ali (JUSPI (Jurnal Sejarah Peradaban Islam), 2023)
The purpose of this study is to find out the background behind the Islamic Circle and the cause of anti-Chinese riots in some areas like Surakarta. In addition to finding out the impact that happens on the indigenous traders in the economy. so that the right method used in this research is with the historical method, which has several stages in the historical method, including data collection (heuristics), Verification (critical source), interpretation (data analysis), and Historiography (history writing). In this case, the Islamic Circuit was formed from the formation of the Islamic Circuit in Surakarta aimed at balancing the economic activities of the Chinese in the process of buying, especially batics. this is what caused anti-Chinese riots.